Ground motion characteristics of the Chi-Chi earthquake of 21 September 1999. - Loh, Chin-Hsiung
The purpose of this paper is to investigate the ground motion characteristics of the Chi-Chi earthquake (21 September 1999) as well as the interpretation of structural damage due to this earthquake. Over 300 strong motion records were collected from the strong motion network of Taiwan for this earthquake. A lot of near field ground motion data were collected. They provide valuable information on the study of ground motion characteristics of pulse like near field ground motions as well as fault displacement. This study includes : attenuation of ground motion both in PGA and spectral amplitude, principal direction, elastic and inelastic response analysis of a SDOF system subjected to near field ground motion collected from this event. The distribution of spectral acceleration and spectral velocity along the Chelungpu fault is discussed. Based on the mode decomposition method the intrinsic mode function of ground acceleration of this earthquake is examined. A long period wave with large amplitude was observed in most of the near source ground acceleration. The seismic demand from the recorded near field ground motion is also investigated with an evaluation of seismic design criteria of Taiwan Building Code.
Keywords: Ground motion analysis; Response spectrum; Seismic demand analysis